Sisal fiber modified construction waste recycled brick as building material: Properties, performance and applications. (December 2022) - Tang, Lei; Liu, Tianle; Sun, Pengliang; Wang, Yuanhao; Liu, Guangyan
Abstract: To study the change rule of mechanical properties of waste ceramic tile recycled brick with different sisal fiber content, this paper studies the influence of sisal fiber on compressive strength, flexural strength, porosity, and saturation coefficient of waste ceramic tile recycled brick, and tests its microstructure by scanning electron microscope and X-ray diffraction, and determines the optimum content of sisal fiber and the change rule of mechanical properties, which provides a reference for further research on modification and application of organic fiber in construction waste brick. The experimental results show that the incorporation of sisal fiber can reduce the compressive strength of recycled bricks from discarded tiles by 19.12 % at most, but the incorporation of sisal fiber at 3.0–4.5 kg/m 3 can significantly improve the flexural strength of recycled bricks, with a maximum value of 36.83 %. With the addition of sisal fiber, the compressive properties and flexural properties of recycled tiles of waste ceramic tiles show different rules, but it shows the optimal balance of performance when the content of 3.0 kg/m 3 is added. The microscopic test results show that the surface crystals of the recycled tiles with 3.0 kg/m 3 and 4.5 kg/m 3 content are neatly arranged, the hydration reaction is more thorough, the CSH gel formed is larger than that of the undoped group, and the 1.5 kg/m 3 group, the internal micropores are filled, and the best performance is consistent with the macroscopic analysis results.